Life-cycle exposure to environmental copper pyrithione causes multigenerational developmental and reproductive toxicity in medaka - Sutapa Debi; Can Tang; Mingfeng Li; Hongdong Fang; Jiezhang Mo; Wenhua Liu (Marine Pollution Bulletin, 2026)

Interactions mechanisms decoding of macadamia protein isolate-procyanidins dimer complexes and synergistic effect for high internal phase Pickering emulsions stabilization - Tingting Chen; Zhipan Wang; Mingfeng Fang; Ming Zhang; Gangjun Guo; Liqing Du; Taotao Dai; Xixiang Shuai (Food Chemistry, 2026)

Capsular polysaccharides of the human gut microbiota: Structural diversity, functional plasticity, and roles in host–microbe mutualism - Ziyi Fang; Mingfeng Ma; Guangli Yu; Qingsen Shang (Carbohydrate Polymers, 2026)

Enhancement of macadamia protein solubility and functionality using combined pH-shift-heat treatment: Role of ionic environment (PBS vs water) - Xixiang Shuai; Mingfeng Fang; David Julian McClements; Tingting Chen; Zhipan Wang; Liqing Du; Ming Zhang; Wei Zhou; Taotao Dai; Jihua Li; Jun Chen (Food Chemistry, 2026)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Degradation and fermentation of hyaluronic acid by Bacteroides spp. from the human gut microbiota - Ziyi Fang; Mingfeng Ma; Yamin Wang; Wei Dai; Qingsen Shang; Guangli Yu (Carbohydrate Polymers, 2024)

Performance Comparison of Sea Cucumber Detection by the Yolov5 and DETR Approach - Xin Yuan; Shutong Fang; Ning Li; Qiansheng Ma; Ziheng Wang; Mingfeng Gao; Pingpeng Tang; Changli Yu; Yihan Wang; José-Fernán Martínez Ortega (Journal of Marine Science and Engineering, 2023)
Sea cucumber detection represents an important step in underwater environmental perception, which is an indispensable part of the intelligent subsea fishing system. However, water turbidity decreases the clarity of underwater images, presenting a challenge to vision-based underwater target detection. Therefore, accurate, real-time, and lightweight detection models are required. First of all, the development of subsea target detection is summarized in this present work. Object detection methods based on deep learning including YOLOv5 and DETR, which are, respectively, examples of one-stage and anchor-free object detection approaches, have been increasingly applied in underwater detection scenarios. Based on the state-of-the-art underwater sea cucumber detection methods and aiming to provide a reference for practical subsea identification, adjacent and overlapping sea cucumber detection based on YOLOv5 and DETR are investigated and compared in detail. For each approach, the detection experiment is carried out on the derived dataset, which consists of a wide variety of sea cucumber sample images. Experiments demonstrate that YOLOv5 surpasses DETR in low computing consumption and high precision, particularly in the detection of small and dense features. Nevertheless, DETR exhibits rapid development and holds promising prospects in underwater object detection applications, owing to its relatively simple architecture and ingenious attention mechanism.

Overexpressing 4-coumaroyl-CoA ligase and stilbene synthase fusion genes in red raspberry plants leads to resveratrol accumulation and improved resistance against Botrytis cinerea - Junxin Zhang; Xihuan Yan; Tiran Huang; Huan Liu; Fang Liu; Meixia Yang; MingFeng Yang; Lanqing Ma (Journal of Plant Biochemistry and Biotechnology, 2023)